Efektivitas Penyuluhan NAPZA Terhadap Tingkat Pengetahuan Siswa Di SMK DD Kabupaten Tanah Laut - Septi Anggraeni; Fakultas Kesehatan Masyarakat UNISKA Banjarmasin (Jurnal Kesehatan Indonesia, 2016)
The Drug abuse (narcotics, psychotropic, and addictive substances) from year to year has been increasing. Drug abuse is a threat and complex problem that can destroy the younger generation. This research is expected to describe the effectiveness of socialization health on the prevention of drug abuse on the knowledge of students. The research was conducted in 2016 on 42 students in SMK DD of Tanah Laut District. This research using methods preeksperimental, using the one group pretest-posttest design. The results of the analysis with the paired sample t-test showed that there were significant differences between the knowledge before and after of the socialization. This research is expected to increase the knowledge students of the drug so as to avoid drug abuse.